Detection and characterization of microRNA expression profiling and its target genes in response to canine parvovirus in Crandell Reese Feline Kidney cells - Chuammitri, Phongsakorn; Vannamahaxay, Soulasack; Sornpet, Benjaporn; Pringproa, Kidsadagon; Patchanee, Prapas (PeerJ (San Francisco, CA), 2020)
MicroRNAs (miRNAs) play an essential role in gene regulators in many biological and molecular phenomena. Unraveling the involvement of miRNA as a key cellular factor during in vitro canine parvovirus (CPV) infection may facilitate the discovery of potential intervention candidates. However, the examination of miRNA expression profiles in CPV in tissue culture systems has not been fully elucidated. In the present study, we utilized high-throughput small RNA-seq (sRNA-seq) technology to investigate the altered miRNA profiling in miRNA libraries from uninfected (Control) and CPV-2c infected Crandell Reese Feline Kidney cells. We identified five of known miRNAs (miR-222-5p, miR-365-2-5p, miR-1247-3p, miR-322-5p and miR-361-3p) and three novel miRNAs (Novel 137, Novel 141 and Novel 102) by sRNA-seq with differentially expressed genes in the miRNA repertoire of CPV-infected cells over control. We further predicted the potential target genes of the aforementioned miRNAs using sequence homology algorithms. Notably, the targets of miR-1247-3p exhibited a potential function associated with cellular defense and humoral response to CPV. To extend the probing scheme for gene targets of miR-1247-3p, we explored and performed Gene Ontology (GO) enrichment analysis of its target genes. We discovered 229 putative targets from a total of 38 enriched GO terms. The top over-represented GO enrichment in biological process were lymphocyte activation and differentiation, marginal zone B cell differentiation, negative regulation of cytokine production, negative regulation of programed cell death, and negative regulation of signaling. We next constructed a GO biological process network composed of 28 target genes of miR-1247-3p, of which, some genes, namely , , , , , and were among the genes with obviously intersected in multiple GO terms. The miRNA-1247-3p and its cognate target genes suggested their great potential as novel therapeutic targets or diagnostic biomarkers of CPV or other related viruses.